Local and Systemic Effects of Topical Betulinic Acid in a Psoriasis-like Inflammation Model in Mice - Fernandes, Flávia S.; Silva, Gustavo S.; Soares, Rafael V.; Ourique, Fabiana; Nakagawa, Tiziane L.D.R.; Martins, Daniel F.; Zamoner, Ariane; Kviecinski, Maicon R. (Planta Medica, 2025)
Psoriasis patients often discontinue oral and injectable treatments due to concerns about both safety and efficacy. Issues such as adverse side effects, limited long-term effectiveness, and fear of potential complications contribute to non-adherence, impacting treatment outcomes and patientsʼ quality of life. Betulinic acid (BA) forms supramolecular aggregates through self-assembly in a hydroalcoholic vehicle, which was hypothesized to have antipsoriatic activity when applied topically. To test this, imiquimod was applied to induce psoriasis-like skin inflammation in mice (except in the untreated group) every 24 hours for 5 days. Two hours after each imiquimod application, the groups received either 100 µL of vehicle (10% glycerol aqueous solution), 0.05 mg/mL clobetasol (Clo), or 0.5 mg/mL BA. At the end of the study, the Psoriasis Area and Severity Index (PASI) was evaluated (n = 12/group), and complete skin clearance time (CSC) was determined in six mice per group. The remaining six mice per group were used to assess acanthosis, lymphocyte and granulocyte infiltration, and Akt and ERK phosphorylation in skin samples, as well as TNFα, IL-17A, IFNγ, and TGFβ levels in serum. To assess treatment safety, we evaluated food and water intake, ambulation pattern, body weight gain, organ weights, and blood parameters. BA significantly reduced CSC time by up to 40% compared to the control and was 10% faster than Clo. Both BA and Clo reduced PASI and acanthosis to approximately one-third of control values, normalized immune cell infiltration and TNFα levels, decreased IL-17A by more than 30%, and reduced p-Akt and p-ERK2. BA uniquely normalized IFNγ levels without causing intolerable toxicity. Using an animal model of psoriatic skin inflammation, our findings support BA as a strong candidate for clinical translation, warranting further studies on its safety, pharmacokinetics, and optimal dosage in humans, potentially leading to randomized controlled trials in psoriasis patients.
Keywords: Dillenia indica; Dilleniaceae; betulinic acid; topical application; psoriasis-like skin inflammation; efficacy-safety